(untitled) (Acta Biomedica Atenei Parmensis, 2024)
[Published Erratum] Dear Editor, Regarding the publication of the following paper: [Corrigendum to] Vincenzo De Sanctis, Shahina Daar , Ashraf T Soliman, Ploutarchos Tzoulis, Mehran Karimi, Salvatore Di Maio, Christos Kattamis. Screening for glucose dysregulation in β-thalassemia major (β-TM): An update of current evidences and personal experience. Acta Biomed 2022;93 (1): e2022158. doi: 10.23750/abm.v93i1.12802. The authors noticed, after having reviewed the original results, that some data reported in text and tables 2 and 3 referring to 234 β-thalassemia major patients with fasting plasma glucose level below 100 mg/dL presenting impaired glucose tolerance (IGT) or thalassemia- related diabetes (ThRD after OGTT, were reported incorrectly (page 5 of published article). Moreover, figure 1 was not assembled. A revised version of both tables and the inclusion of figure 1 have been prepared. All authors have approved the corrigendum and regret their oversight in allowing these errors. The authors thank the Editor of Acta Biomedica for allowing them the opportunity to publish this corrigendum and apologize to the readership for any inconvenience caused. Sincerely Vincenzo De Sanctis